Analisis Peran Pemuda Sarjana Penggerak Pembangunan Di Pedesaan (PSP3) Terhadap Pembagunan Desa Di Kabupaten Pakpak Bharat - Juwita Rahmadani Manik (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2016)
PSP3 (village development initiators of young academicians) program is intended to accelerate development through the role of youth, especially young people in villages, in various public activities. These activities can affect the dynamic of villagers' lives, develop youth potentially, and increase the welfare of the youth and the elderly in villages. The research was conducted at Prongil Village, Tinada Subdistrict, and at Kuta Jungak Village, Siempat Ribe Subdistrict, Pakpak Bharat District, from May until July 2015. It was about PSP3 in village development in Pakpak Bharat District, using the survey method. The role of PSP3 in people's income organized by PSP3 was analyzed by using an independent paired t-test and the role of PSP3in the level of people's knowledge and skills in farming, especially in red chilli agribusiness, was analyzed by using correlation test. The result of the research showed that people's income organized by PSP3 increased which was indicated by the average income of Rp. 951.67 before the program was conducted became Rp. 1435.85 after the program was conducted. The increase in people's income varied, from Rp. 300,000 until Rp. 650,000. The result of the correlation test showed that the role of youth in improving people's knowledge and skills in farming, especially in red chilli agribusiness, had a significant correlation as follows: correlation of the level of knowledge and skill with independence was at a p-value of 0.185 > 0.05 which indicated that there was a significant correlation. P-value in knowledge and skill with assistance = 0.000<0.05 which indicated that there was a significant correlation and p-value assistance with independence = 0.006 < 0.05 which indicated that there was a significant correlation. The conclusion of the research was that there was the role of youth in improving people's knowledge and skill after PSP3 program was conducted and after there was assistance from PSP3 personnel in farming, especially in red chili agribusiness.